2019
DOI: 10.1186/s12864-019-6288-7
|View full text |Cite
|
Sign up to set email alerts
|

A novel graph theoretical approach for modeling microbiomes and inferring microbial ecological relationships

Abstract: BackgroundMicrobiomes play vital roles in shaping environments and stabilize them based on their compositions and inter-species relationships among its species. Variations in microbial properties have been reported to have significant impact on their host environment. For example, variants in gut microbiomes have been reported to be associated with several chronic conditions, such as inflammatory disease and irritable bowel syndrome. However, how microbial bacteria contribute to pathogenesis still remains uncl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The Genus Bacteroides and Eubacterium have multiple subgroups, and the Pectinophilus group was selected for Bacteroides, and the nodatum group was selected as a stand-in for Eubacterium, and both passed our filtering procedures. In the last example, the authors had used a linear discriminant analysis effect size approach to determine three important taxa, two from the Family-level and one from the Order level, all of which are present in our features (Kim et al, 2019).…”
Section: Evaluation Of Machine Learning Resultsmentioning
confidence: 99%
“…The Genus Bacteroides and Eubacterium have multiple subgroups, and the Pectinophilus group was selected for Bacteroides, and the nodatum group was selected as a stand-in for Eubacterium, and both passed our filtering procedures. In the last example, the authors had used a linear discriminant analysis effect size approach to determine three important taxa, two from the Family-level and one from the Order level, all of which are present in our features (Kim et al, 2019).…”
Section: Evaluation Of Machine Learning Resultsmentioning
confidence: 99%
“…The authors of the Kim et al 60 study analyzed data originally collected by Eun et al 67 but only the former study was retrieved by our systematic search strategy; thus, this dataset is referred to as Kim et al…”
Section: Methodsmentioning
confidence: 99%
“…we found that, in Liaoning, Henan, and Shanghai, sodium consumption was positively associated with pathogenic bacteria including Staphylococcus, which causes a wide variety of severe infections (38), and Moraxellaceae, a biomarker for Crohn disease (47), indicating that high sodium intake may increase the susceptibility to gut infection and inflammation. Indeed, sodium exposure has been shown to enhance proinflammatory cytokine production in human intestinal mononuclear cells and a highsodium diet exacerbated colitis in mice (48).…”
Section: Discussionmentioning
confidence: 79%